Rheological properties of magnetic and electro-active nanoparticles in non-polar liquids - Libor, Zsuzsanna; Wilson, Stephen A.; Zhang, Qi (Springer Science Business Media, 2011)
The rheological properties of two non-polar liquids [silicone oil or perfluorinated oil (FC70)] containing various types of particles, barium titanate, nickel and iron oxide, were investigated as functions of solid loading, particle size and shear rate. All the particles were synthesised in- house. The viscosities of either silicone oil or FC70 containing different solid loadings (10, 20 and 30 g/L) were measured over the shear rate range of 0.10-10 s(-1). All the nanofluids showed shear-thinning behaviour within this range and the viscosities increased with the increase of concentrations of nanoparticle and with the decrease of particle size. The highest increase of viscosity was found to be caused by nickel particles in silicone oil due to the formation of Ni network.
Keywords: heat-transfer thermal-conductivity aqueous suspensions nano-fluids nanofluids viscosity behavior nanocomposites particles powders